Cohort profile of the UK Biobank: diagnosis and characteristics of cerebrovascular disease. Issue 3 (22nd March 2016) - Hewitt, J; Walters, M; Padmanabhan, S; Dawson, J
Abstract : Purpose: The UK Biobank is a large-scale biomedical resource, containing sociodemographic and medical information, including data on a previous diagnosis of stroke or transient ischaemic attack (TIA). We described these participants and their medication usage. Participants: We identified participants who either self-reported or were identified from a nurse-led interview, having suffered a stroke or a TIA and compared them against participants without stroke ort TIA. We assessed their risk factor burden (sex, age, deprivation, waist to hip ratio (WHR), hypertension, smoking, alcohol intake, diabetes, physical exercise and oral contraception use (oral contraceptive pill, OCP)) and medication usage. Findings to date: We studied 502 650 people (54.41% women), 6669 (1.23%) participants self-reported a stroke. The nurse-led interview identified 7669 (1.53%) people with stroke and 1781 (0.35%) with TIA. Hypertension, smoking, higher WHR, lower alcohol consumption and diabetes were all more common in people with cerebrovascular disease (p<0.0001 for each). Women with cerebrovascular disease were less likely to have taken the OCP (p=0.0002). People with cerebrovascular disease did more exercise (p=0.03). Antithrombotic medication was taken by 81% of people with stroke (both self-report and nurse-led responders) and 89% with TIA. For self-reported stroke, 63% were taking antithrombotic and cholesterol medications, 54% taking antithrombotic and antihypertensive medications and 46% taking all 3. For the nurse-led interview and TIA, these figures were 65%, 54% and 46%, and 70%, 53% and 45%, respectively. Future plans: The UK Biobank provides a large, generalisable and contemporary data source in a young population. The characterisation of the UK Biobank cohort with cerebrovascular disease will form the basis for ongoing research using this data source.